Special Declaration on the Defense of Democracy and the Constitutional Order in the Community of Latin American and Caribbean States (CELAC) - Estados Latinoamericanos y Caribeños, Comunidad de (2012)
Declaration made by the Heads and Heads of State and Government of the Latin American and Caribbean countries, meeting in Caracas, Bolivarian Republic of Venezuela, on December 3, 2011 in the framework of the Foundational Summit of the Community of Latin American and Caribbean States (CELAC).